DNA Amplification of Meat Tenderness Gene of Bali Cattle - Agus Susilo; Tety Hartatik; Wayan Tunas Artama (Faculty of Animal Science Universitas Brawijaya, 2011)
The aim of this study was to find out DNA band pattern as a result of amplification using DNA primer from meat tenderness gene of Bali cattle. Sample used in this study was DNA isolated from blood Bali cattle. Blood samples was collected in heparin tubes from jugular vein. Leucocyte cells were isolated using RBCs (Red Blood Cells) lysis buffer. To get DNA fragmen, marbling and meat tenderness gene were amplified by using DNA primer for for meat tenderness (forward: 5’–CTACCGGGACGTCAACCT-3’; reverse: 5’-GGTTGTCGGGGTAGCTCA-3’). The size of DNA fragment were 210 bp. Key words: Bali cattle, meat tenderness gene